2006
DOI: 10.1128/jb.00246-06
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Exported via the PrsD-PrsE Type I Secretion System and the Acidic Exopolysaccharide Are Involved in Biofilm Formation byRhizobium leguminosarum

Abstract: The type I protein secretion system of Rhizobium leguminosarum bv. viciae encoded by the prsD and prsE genes is responsible for secretion of the exopolysaccharide (EPS)-glycanases PlyA and PlyB. The formation of a ring of biofilm on the surface of the glass in shaken cultures by both the prsD and prsE secretion mutants was greatly affected. Confocal laser scanning microscopy analysis of green-fluorescent-protein-labeled bacteria showed that during growth in minimal medium, R. leguminosarum wild type developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(181 citation statements)
references
References 63 publications
6
167
0
8
Order By: Relevance
“…It is interesting, however, that similar phenotypes have been linked to biofilm production (22,26,73). Biofilms have recently been shown to occur in Rhizobia (23,62,65). In Rhizobium leguminosarum, the PrsD-PrsE secretion system was shown to be involved in biofilm production (65).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting, however, that similar phenotypes have been linked to biofilm production (22,26,73). Biofilms have recently been shown to occur in Rhizobia (23,62,65). In Rhizobium leguminosarum, the PrsD-PrsE secretion system was shown to be involved in biofilm production (65).…”
Section: Discussionmentioning
confidence: 99%
“…We used chambered coverslides, whereby the base of the culture chamber forms a coverslip, to visualize biofilm formation, as this allowed us to visualize aggregates as they sedimented. Chambered coverslides have also been used in studies of R. leguminosarum [11], S. meliloti [46] and X. campestris [47] biofilms. We found that the exoS mutant forms an inhomogeneous structure, consisting of interlinked aggregates separated by gaps that are characteristic of the 'water channels' described in many biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on rhizobial biofilms, many have used chambered coverslides, which consist of a coverslip with culture chambers mounted on top, that are imaged using an inverted confocal microscope [11,46,47]. We used the same arrangement in our work as it allowed the visualization of the sediment that formed as bacteria aggregate and sediment.…”
Section: Application Of Xanthan To S Meliloti Cultures and Applicatimentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the degree of EPS polymerization is important for proper development of biofilms in rhizobia. Mutant strains of R. leguminosarum, having mutations in genes involved in EPS processing (prsD and prsE encoding components of the type I protein secretion system and plyB encoding glycanase), are only able to form biofilms of immature structure (Russo et al 2006).…”
Section: Discussionmentioning
confidence: 99%